APPLICATION OF REPRESENTATIVES OF THE APIACEAE FAMILY IN PHARMACEUTICS AND MEDICINE - Zamira Djumayeva, Norqulova Dilshoda (International Journal of Literature and Language Studies, 2026)
This article highlights the significance of plants belonging to the Apiaceae family in pharmaceuticals and folk medicine. Members of the lily family contain essential oils, flavonoids, alkaloids, vitamins, and other biologically active substances, which are widely used in the treatment and prevention of various diseases. The article analyzes the chemical composition and medicinal properties of cumin, anise, cilantro, dill, and other medicinal plants. The prospects for using these plants in the production of medicines in the pharmaceutical industry are also considered. The research findings demonstrate the significant role of members of the Apiaceae family in medicine and pharmacy.